Genetic characterization of methicillin-resistant staphylococcus aureus isolates from human bloodstream infections: detection of mlsb resistance - Silva, Vanessa (2020)
In this study we aimed to characterize antimicrobial resistance in methicillin-resistant Staphylococcus aureus (MRSA) isolated from bloodstream infections as well as the associated genetic lineages of the isolates. Sixteen MRSA isolates were recovered from bacteremia samples from inpatients between 2016 and 2019. The antimicrobial susceptibility of these isolates was tested by the Kirby–Bauer disk diffusion method against 14 antimicrobial agents. To determine the macrolide–lincosamide–streptogramin B (MLSB) resistance phenotype of the isolates, erythromycin-resistant isolates were assessed by double-disk diffusion (D-test). The resistance and virulence genes were screened by polymerase chain reaction (PCR). All isolates were characterized by multilocus sequence typing (MLST), spa typing, staphylococcal chromosomal cassette mec (SCCmec) typing, and accessory gene regulator (agr) typing. Isolates showed resistance to cefoxitin, penicillin, ciprofloxacin, erythromycin, fusidic acid, clindamycin, and aminoglycosides, confirmed by the presence of the blaZ, ermA, ermC, mphC, msrA/B, aac(6’)-Ie-aph(2’’)-Ia, and ant(4’)-Ia genes. Three isolates were Panton–Valentine-leukocidin-positive. Most strains (n = 12) presented an inducible MLSB phenotype. The isolates were ascribed to eight spa-types (t747, t002, t020, t1084, t008, t10682, t18526, and t1370) and four MLSTs (ST22, ST5, ST105, and ST8). Overall, most (n = 12) MRSA isolates had a multidrug-resistance profile with inducible MLSB phenotypes and belonged to epidemic MRSA clones.